Advancing healthcare through mobile collaboration: a survey of intelligent nursing robots research - Wang, Boyuan; Chen, Shanji; Xiao, Gexin (Frontiers in Public Health, 2024)
Mobile collaborative intelligent nursing robots have gained significantconsider-20 able attention in the healthcare sector as an innovative solution to address the challenges 21 posed by the increasing aging population and limited medical resources. This article pro-22 vides a comprehensive overview of the research advancements in this field, covering hos-23 pital care, home elderly care, and rehabilitation assistance. In hospital settings, these ro-24 bots assist healthcare professionals in tasks such as patient monitoring, medication man-25 agement, and bedside care. For home elderly care, they enhance the elderly's sense of se-26 curity and quality of life by offering daily life support and monitoring. In rehabilitation, 27 these robots provide services such as physical rehabilitation training and social interaction 28 to facilitate patient recovery. However, the development of intelligent nursing robots 29 faces challenges in technology, ethics, law, and user acceptance. Future efforts should fo-30 cus on improving robots' perceptual and cognitive abilities, enhancing human-robot in-31 teraction, and conducting extensive clinical experiments for broader applications.